Evaluation of the SIKAB Application Program in Improving Employee Discipline at the Bintan District Education Office - Shanti, Dewi; Samin, Rumzi; Subiyakto, Rudi (Journal of Governance and Social Policy, 2025)
This research refers to the problem of improving employee performance and discipline at the Bintan Regency Education Office and the alternative step taken by the Government is to create the SIKAB Application. The purpose of this study is to evaluate the steps taken by the Bintan Regency government in overcoming the problems caused by the SIKAB application and the impact felt by employees after using it. The method used is descriptive qualitative with a case study approach, data collection is done by means of observation, interviews, and documentation. The results showed that the application still had an impact on increasing employee discipline, but not with applications that still experienced errors and did not have a remote radar feature. Not only that, special development and further evaluation are still needed in overcoming application problems and what kind of performance is carried out by employees of the Bintan Regency Education Office. The conclusion in this study found that the SIKAB application has been running well, as evidenced by the existence of application development and various other problems related to improving employee performance and discipline at the Bintan Regency Education Office.